Development and Improvement of Catfish Cultivation Productivity in Balongmojo Village, Mojokerto - Widagdo, Reza Sarwo; Hariadi, Balok; Wardah, Izzah Aula; Ardianik, Ardianik; Kusmiyati, Kusmiyati (Perkumpulan Kualitama Edukatika Indonesia, 2025)
Balongmojo Village is an entrepreneurial village in Mojokerto that has great potential in the livestock sector, especially catfish cultivation. The community service carried out aims to increase the productivity and sustainability of fisheries businesses in the village through the application of simple and environmentally friendly technology. Community service activities carried out include: (1) development of alternative feed based on agricultural waste (tofu dregs) for catfish; (2) making probiotics to improve catfish health; (3) managing catfish pond waste into liquid fertilizer; and (4) implementing an IoT-based automatic feeding system. The results of the study showed that the application of this technology was able to improve the quality of pond water and the growth of catfish. In addition, the use of organic waste also contributes to increasing soil fertility and reducing environmental pollution. Overall, this community service program has had a positive impact on improving the welfare of the Balongmojo Village community through increasing income, improving the environment, and developing community capacity in adopting modern technology.